PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPESTUDENTFACILITATOR AND EXPLAINING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWAKELAS VIII SMPN 8 PARIAMAN TAHUN PELAJARAN 2013/2014 - Roliana, Rici; K, Delsi; Cesaria, Anna (Pendidikan Matematika, 2013)
The background of thisresearchby thestudentslack of understanding ofmathematical conceptandstudents perceptions ofmathstatingitdifficultandtedious. Thisstudyaims to determinewhetherstudents understanding of mathematical conceptby applyingactive learningstrategiestype ofStudentFacilitatorandExplainingbetter thanstudentsunderstanding ofconcept mathematicthatapplytoconventional teachingclass VIIISMP8Pariamanacademic year2013/2014.This type of reseach is experimental. Technique of random sampling VIII.2 as experimental class and VIII.3 as control class. Instrumentused wasthe ultimate teststudentsunderstanding of conceptmathematicwith 16itemshadreliabilityessay0.804. Data obtainedin the analysisby using anormality test, homogeneity testandt-test. Based onthe analysis of dataobtained bythe averageclassroomstudent learning outcomes75.903experimentwashigher thanthe control classis52.203. Soit can be concludedthat thestudentsunderstanding ofmathematicalconceptsusingactivelearningstrategiestype ofStudentFacilitatorandExplainingbetter thanconventional learninginclassVIIISMP8Pariamanacademic year2013/2014on thelevel of 95%.